2008
DOI: 10.1186/2046-0481-61-12-809
|View full text |Cite
|
Sign up to set email alerts
|

Herd and within-herd BoHV-1 prevalence among Irish beef herds submitting bulls for entry to a performance testing station

Abstract: Infectious bovine rhinotracheitis (IBR), caused by bovine herpes virus 1 (BoHV-1), may result in various clinical consequences, including severe respiratory disease and conjunctivitis, venereal disease and reduced reproductive performance and abortion. This paper presents the serosurveillance findings from an intake of bulls into a performance testing station in Ireland during November 2007. The herd and within-herd BoHV-1 prevalence in 53 Irish beef herds and the risk factors for infection in these herds were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 17 publications
4
23
1
Order By: Relevance
“…All calves in the present study had elevated maternally derived antibodies to BRSV and BoHV-1 (wt) by 12 h post-birth. Cowley, Clegg, Doherty, and More (2011) reported herd-level seroprevalence of BoHV-1 in Ireland at a rate of 74.9%, which is in agreement with previous findings for bulls (O'Grady et al, 2008), and with the results of the present study. Our findings showed that the cows had total BoHV-1 wt antibodies circulating in their blood; this indicated that these animals had been naturally exposed to BoHV-1 at some stage in their lifetime.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All calves in the present study had elevated maternally derived antibodies to BRSV and BoHV-1 (wt) by 12 h post-birth. Cowley, Clegg, Doherty, and More (2011) reported herd-level seroprevalence of BoHV-1 in Ireland at a rate of 74.9%, which is in agreement with previous findings for bulls (O'Grady et al, 2008), and with the results of the present study. Our findings showed that the cows had total BoHV-1 wt antibodies circulating in their blood; this indicated that these animals had been naturally exposed to BoHV-1 at some stage in their lifetime.…”
Section: Discussionsupporting
confidence: 93%
“…In Ireland, limited information has emerged regarding bovine herpesvirus 1 (BoHV-1) infection, albeit from a subset of Irish beef herds (O'Grady, ONeill, Collins, Clegg, and More, 2008) of which 73.2% were seropositive. BoHV-1 virus causes respiratory infections and abortions in cattle, and is an important component of the bovine respiratory disease complex, which causes a considerable economic loss worldwide (Chowdhury, Wei, Weiss, Pannhorst, and Paulsen, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have consistently reported markedly increased seroprevalence in both dairy and beef herds in Ireland. An investigation into the inter- and intra-herd seroprevalence of BoHV-1 in beef herds supplying bulls to an Irish performance testing station found herd prevalence to be 73.2% with a mean within herd prevalence of 28% (±20%) [46]. …”
Section: Reviewmentioning
confidence: 99%
“…infection (van Schaik et al, 1998;O'Grady et al, 2008). In this respect, percentage of inter-herd movements was used as a measure of biosecurity within the herds sampled in the present study.…”
Section: Risk Factors For Bhv-1 Pathogenicitymentioning
confidence: 99%